2019
DOI: 10.1002/ijc.32166
|View full text |Cite
|
Sign up to set email alerts
|

X chromosome‐linked long noncoding RNA lnc‐XLEC1 regulates c‐Myc‐dependent cell growth by collaborating with MBP‐1 in endometrial cancer

Abstract: LncRNAs (long noncoding RNAs) are noncoding transcripts that are more than 200 nt long and have been described as the largest subclass in the noncoding transcriptome in humans. Although studies of lncRNAs in cancer have been continuing for a long time, no much has been known about X chromosome‐linked lncRNAs. Here, by using RNA‐seq we report the identification of a new X chromosome‐linked lncRNA (lnc‐XLEC1) that is aberrantly downregulated during the development of endometrial carcinoma (EC). The overexpressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Furthermore, c-Myc, as a transcription factor, is a proto-oncogene and in human cancers, c-Myc is frequently constitutively expressed, which results in enhanced expression of various cell growth-related and apoptosis-resistant genes to promote carcinogenesis 32. Previous studies showed that a remarkable association of aberrant lncRNA expression with c-Myc 7,28,3335. These publications demonstrated that c-Myc promoted normal cells to neoplastic transformation by affecting a drastic change in the number and the type of gene expression, including various lncRNAs in different human cancers 28.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, c-Myc, as a transcription factor, is a proto-oncogene and in human cancers, c-Myc is frequently constitutively expressed, which results in enhanced expression of various cell growth-related and apoptosis-resistant genes to promote carcinogenesis 32. Previous studies showed that a remarkable association of aberrant lncRNA expression with c-Myc 7,28,3335. These publications demonstrated that c-Myc promoted normal cells to neoplastic transformation by affecting a drastic change in the number and the type of gene expression, including various lncRNAs in different human cancers 28.…”
Section: Discussionmentioning
confidence: 99%
“…And lncRNA can bind to chromatin modifying factors or other transcriptional factors 18,25. Previous studies revealed that different lncRNAs are able to directly bind to c-Myc and affect c-Myc transcriptional activity 7,28,33,34. For instance, lncRNA MINCR was shown to bind and affect c-Myc transcriptional activity by recruiting an MYC co-activator to c-Myc-targeted gene promoters for activation of their transcription in cells,39 while lncRNA PDIA3P26 and PCGEM140 showed to bind to c-Myc to induce gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs are reported to be involved in a range of developmental processes and diseases, especially human cancers 7 . Several lncRNAs, such as lncRNA lnc-XLEC1, lncRNA LINC00672, and lncRNA HAND2-AS1, have been identified in EC pathogenesis [8][9][10] . Located at an intergenic region between two protein-coding genes (myocyte enhancer factor 2C and transmembrane protein 161B), LINC00461 is reported to be dysregulated in several types of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…This inactivation led to reduced c-Myc expression as well as Snail and N-cadherin and the overexpression of PI3K in α-Enolase silenced endometrial cancer cells reversed this effect [ 82 ]. However, c-Myc promoter binding protein 1 (MBP-1), an alternative translation product of α-Enolase, has been shown to suppress c-Myc expression, which reduced the proliferation and migration of endometrial cells [ 83 ]. Targeting the Hedgehog signaling pathway, which has been suggested to maintain CSCs [ 84 ], significantly inhibited the growth of endometrial cancer cells with a concomitant reduced expression of cyclin D1 and N-Myc [ 85 ].…”
Section: Targeting Signaling Pathways In Endometrial Cancer Stem Cellsmentioning
confidence: 99%